Qualitative and Quantitative Analysis of Certain Aspects of the Cytotoxic and Genotoxic Hazard of Hospital Wastewaters by Using a Range of In Vitro Assays - Janousek, Stanislav; Vlkova, Alena; Jirova, Gabriela; Kejlova, Kristina; Krsek, Daniel; Jirova, Dagmar; Kandarova, Helena; Wittlingerova, Zdenka; Heinonen, Tuula; Mannerstrom, Marika; Maly, Marek (Alternatives to laboratory animals, 2021)
Health care facilities and hospitals generate significant amounts of wastewater which are released into the sewage system, either after a preliminary treatment or without any further treatment. Hospital wastewater may contain large amounts of hazardous chemicals and pharmaceuticals, some of which cannot be eliminated entirely by wastewater treatment plants. Moreover, hospital effluents may be loaded with a plethora of pathogenic microorganisms or other microbiota and microbiome residues. The need to monitor hospital effluents for their genotoxic hazard is of high importance, as detailed information is scarce. DNA-based information can be acquired directly from samples through the application of various molecular methods, while cell-based biomonitoring assays can provide important information about impaired cellular pathways or mechanisms of toxicity without prior knowledge of the identity of each toxicant. In our study, we evaluated samples of chlorinated hospital wastewater discharged into the sewage system after this disinfection process. The assessment of cytotoxicity, genotoxicity and mutagenicity of the hospital effluents was performed in vitro by using a broad battery of biomonitoring assays that are relevant for human health effects. All the tested hospital wastewater samples could be classified as potentially genotoxic, and it is concluded that the microbiota present in hospital wastewater might contribute to this genotoxic potential.
Keywords: odpadní voda; Mutagenicity Tests; nemocnice; Humans; genotoxicity; Water Pollutants, Chemical; wastewater safety; Hospitals; in vitro testing; Wastewater; poškození DNA; testy genotoxicity; DNA Damage; microbiota contamination; Waste Water; hospital effluents; cytotoxicity; lidé; chemické látky znečišťující vodu; health hazard